David Wells' Psychic Secrets - Wells, David (Carlsbad Hay House, Inc., 2009)
In his latest incredible work, former Most Haunted presenter David Wells examines real life experiences to uncover the extraordinary truth behind psychic events. What really causes possessions and past lives, and why is visualisation and meditation important? Is it to allay our own fears, or to communicate with the ghosts of those long passed - or is it something more?From the young girl who learned how to communicate with her disabled son to a soul level, to the extraordinary power of past life regression, you'll discover the practical side of what really makes things ""go bump in the night""
Keywords: Parapsychology